Drug Delivery: Bioinspired Mechano‐Sensitive Macroporous Ceramic Sponge for Logical Drug and Cell Delivery (Adv. Sci. 6/2017). Issue 6 (June 2017) - Xu, Changlu; Wei, Zhihao; Gao, Huajian; Bai, Yanjie; Liu, Huiling; Yang, Huilin; Lai, Yuekun; Yang, Lei
Abstract : On‐demand, ultra‐high precision delivery of molecules and cells is of great importance in the field of controlled release. In article number1600410, inspired by sea sponges, Lei Yang, Yuekun Lai, and co‐workers design and fabricate a biomimetic macroporous ceramic composite sponge which reveals unique precise AND logic release behaviors of molecules and cells in response to dual‐gates of moisture and pressure (or strain).